The new futility? The rhetoric and role of “suffering” in pediatric decision-making - Salter, Erica K. (Nursing ethics, 2020)
This article argues that while the presence and influence of “futility” as a concept in medical decision-making has declined over the past decade, medicine is seeing the rise of a new concept with similar features: suffering. Like futility, suffering may appear to have a consistent meaning, but in actuality, the concept is colloquially invoked to refer to very different experiences. Like “futility,” claims of patient “suffering” have been used (perhaps sometimes consciously, but most often unconsciously) to smuggle value judgments about quality of life into decision-making. And like “futility,” it would behoove us to recognize the need for new, clearer terminology. This article will focus specifically on secondhand claims of patient suffering in pediatrics, but the conclusions could be similarly applied to medical decisions for adults being made by surrogate decision-makers. While I will argue that suffering, like futility, is not sufficient wholesale justification for making unilateral treatment decisions, I will also argue that claims of patient suffering cannot be ignored, and that they almost always deserve some kind of response. In the final section, I offer practical suggestions for how to respond to claims of patient suffering.